2004
DOI: 10.1128/jcm.42.3.1348-1352.2004
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Human Herpesvirus 7 DNA by Loop-Mediated Isothermal Amplification

Abstract: The reliability of loop-mediated isothermal amplification (LAMP), initially developed for the detection of human herpesvirus 7 (HHV-7), was evaluated in this study. Although a LAMP product was detected in HHV-7 DNA, neither HHV-6 nor human cytomegalovirus DNA produced a product. When agarose gel electrophoresis was used for the detection of LAMP products, the sensitivity of a 30-min HHV-7 LAMP reaction reached 250 copies/tube. The use of turbidity for the detection of the LAMP products gave a sensitivity of 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
31
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 21 publications
1
31
0
Order By: Relevance
“…An accurate and rapid diagnosis system for periodontitis is essential for periodontal treatment. Several recent reports have demonstrated the usefulness of the LAMP method (10,11,17,26,27,33,49). Therefore, we focused on the LAMP method for the rapid detection of periodontopathic bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…An accurate and rapid diagnosis system for periodontitis is essential for periodontal treatment. Several recent reports have demonstrated the usefulness of the LAMP method (10,11,17,26,27,33,49). Therefore, we focused on the LAMP method for the rapid detection of periodontopathic bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Although the capability to distinguish between HSV-1 and HSV-2 infection is not crucial for correct administration of antiviral drugs, this discrimination is important from an epidemiological or public health standpoint. As a consequence of the experiment used for determination of the assay sensitivity, it was suggested that the turbidity assay is a less sensitive detection method than agarose gel electrophoresis, as previously suggested (23). However, the turbidity assay is more appropriate for bedside monitoring due to its ease and rapidity.…”
mentioning
confidence: 99%
“…This method also exhibits extremely high amplification efficiency, due in part to its isothermal nature; as there is no time lost due to changes in temperature and the reaction can be conducted at the optimal temperature for enzyme function, the inhibition reactions that often occur at later stages of typical PCR amplifications are less likely to occur. Thus, this method could potentially be a valuable tool for the rapid diagnosis of infectious diseases (5,8,9,12,19,23) in both commercial and hospital laboratories. In this study, we sought to establish a LAMP-based HSV typespecific DNA amplification method and examine its reliability for the detection of HSV DNA from clinical specimens.…”
mentioning
confidence: 99%
“…The technique, termed loop-mediated isothermal amplification (LAMP), requires a set of conditions and primers different from those used for PCRs (8,12,14,15). LAMP assays have now been reported for several pathogens (8,9,12,14,15,18,20). The reaction typically occurs over 30 to 60 min under isothermal conditions with temperatures ranging from 60 to 65°C and can be conducted with a simple heating block.…”
mentioning
confidence: 99%